Effect of Ragi Concentration on the Physical and Chemical Characteristics of Kepok Banana Tape (Musa paradisiaca L.) - Siti Nuryanti; Dinda Ulan Daini; Tahril; Sitti Rahmawati; Arwansyah (Jurnal Penelitian Pendidikan IPA, 2025)
Banana tape is one of the innovations in processing bananas into new processed products that can be enjoyed by the community, which is almost the same as making tape in general. The purpose of this study was to determine the right variation of ragi concentration on the physical and chemical characteristics of kepok banana tape. This type of research is experimental with the Completely Randomized Design (RAL) method with variations in ragi concentration, namely 0.5 grams, 1 gram, 1.5 grams, 2 grams and 2.5 grams with a fermetation time of 3 days. The parameters of this study include physical analysis (taste, flavor, color and texture) and chemical analysis (glucose, alcohol and pH). The results showed that ragi concentration of 0.5 gram produced the best organoleptic test of taste 3.75, aroma 3.4, color 3.6 and texture 3.45. Chemical tests showed that a ragi concentration of 1.5 grams produced the best results in glucose levels of 7.9%, alcohol 1.24% and pH 4.41. This study has the potential to be used as a contextual chemistry learning medium, particularly in understanding fermentation processes, pH changes, and biochemical transformations in everyday food products.